2012
DOI: 10.1097/ccm.0b013e31822f08b9
|View full text |Cite
|
Sign up to set email alerts
|

Delayed inhibition of angiotensin II receptor type 1 reduces secondary brain damage and improves functional recovery after experimental brain trauma*

Abstract: The results indicate that angiotensin II receptor type 1 plays a key role in the development of secondary brain damage after brain trauma. Inhibition of angiotensin II receptor type 1 with a delay of up to 4 hrs after traumatic brain injury effectively reduces lesion volume. This reduction makes angiotensin II receptor type 1 a promising therapeutic target for reducing cerebral inflammation and limiting secondary brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 21 publications
7
66
1
1
Order By: Relevance
“…We therefore investigated the effect of administering candesartan to mice just before they received a controlled cortical impact (CCI) injury to determine whether short-or long-term inhibition of central AT 1 Rs would reduce the cortical and hippocampal damage and hence protect against cognitive impairment. While we were completing these data, a report was published demonstrating that administration of low doses of candesartan to mice within 4 h of TBI prevented secondary brain damage and reduced cerebral inflammation at 24 h post-injury (Timaru-Kast et al, 2012). Our studies confirm and extend these observations.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…We therefore investigated the effect of administering candesartan to mice just before they received a controlled cortical impact (CCI) injury to determine whether short-or long-term inhibition of central AT 1 Rs would reduce the cortical and hippocampal damage and hence protect against cognitive impairment. While we were completing these data, a report was published demonstrating that administration of low doses of candesartan to mice within 4 h of TBI prevented secondary brain damage and reduced cerebral inflammation at 24 h post-injury (Timaru-Kast et al, 2012). Our studies confirm and extend these observations.…”
Section: Introductionsupporting
confidence: 79%
“…Indeed, beneficial effects of candesartan after stroke have been shown for doses that are not hypotensive (Omura-Matsuoka et al, 2009). The results of Timaru-Kast et al (2012), show that post-injury administration of candesartan up to 4 h after injury are beneficial to recovery when assessed at 24 h after injury. We have shown that the beneficial cognitive effects of candesartan can be detected up to 28 days after injury.…”
Section: Neuroprotection By Candesartan After Tbimentioning
confidence: 63%
See 1 more Smart Citation
“…This test has been established for mouse TBI and evaluates motor function, alertness, balancing, and general behavior [17].…”
Section: Assessment Of Functional Outcomementioning
confidence: 99%
“…The hypermetabolic syndrome develops in different extremal states and in patients with cerebral trauma also [11]. Secretion of catecholamines, glucocorticoids and angiotensin is stimulated by trauma and stress [12]. Oxygen necessity of brain increase, but disorders of circulation, accumulation of lactate, formation of acidosis lead to hypoxia [13].…”
Section: Introductionmentioning
confidence: 99%